Genetic Diversity and Characterization of Indigenous Rhizobium Leguminosarum Biovar Viciae Isolates of Cool-Season Food Legumes Grown in the Highlands of Ethiopia - Tegegn, Negash Demissie (2006)
Cool-season food legumes (CSFLs) are legumes of the temperate cool subtropical origin. In Ethiopian context these legumes encompass 5 legumes such as faba bean (Vicia faba), field pea (Pisum sativum), lentil (Lens culinaris), Chickpea (Cicer arietinum) and Grasspea (Lathyrus sativus) and are cultivated on the highlands. These legumes have high economic values and provide rich protein sources for human and animal consumption. Although it was reported that, a few species taxonomically related to cultivated CSFL exist in Ethiopian. Thus, there is reason to believe that Ethiopian soils harbour diverse rhizobial isolates, which form symbiotic relationships with CSFLs. In general, there is little or no information is available on the diversity CSFL rhizobia across the country. This indicates that the extent and divergent of the local rhizobial populations belonging to the long cultivated lands are yet to discover. Thus, the importance of characterizing indigenous rhizobia cannot be overemphasized. It is important to establish which rhizobia nodulate which host(s) and how effectively and which rhizobia predominate which region in order to develop broad host range inoculants in the country. Hence, the current study was conducted with the objectives to isolate, characterise, and determine the morphological, biochemical, and genetic diversity of rhizobial syrnbionts to CSFLs grown of Ethiopia, and to determine inoculation effects of selected elite strains against introduced/exotic strains on the symbiotic growth and development of lentil (Lens culinaris). Over 150 indigenous Rhizobium species, syrnbionts to CSFLs, were collected from farmers' fields in the highlands of Ethiopia and categorized based on their rhizosphere pH and their agro-ecological zones (AEZ) origin. These isolates were characterised for their colony morphology, host specifity, cell growth rate and mean generation time, acid producing and intrinsic antibiotic resistance (IAR) characteristics. However, a more comprehensive and detail physiological (ATR, STL, IAA, C SUP), and genetic (RAPD, RE RFLP) characterization studies were made apparently for 90 representative isolates of the 150 isolates. Finally, field inoculation experiment was conducted on lentil plant using two elite and 2 exotic inoculant strains. The collection, isolation, colony morphological characterization, and field experiment studies were canied on in Ethiopia, while the physiological and genetic characterization studies were at the Universiti Putra Malaysia WPM) laboratories in Malaysia. The study recognized the different rhizosphere pH for the host and existing agroecological zones (AEZs) for the initial isolates sampling points and used as a tool to categorize the bulk rhizobial isolates. Thus, isolates constituted 3 and 4 categories for PERWsTRKbAN WTAN A W L SAW rhizosphere pH and AEZs, respectively. All isolates were Gram ne~%@&hdViY8A Ieguminosarum bv. viciae species. Results of the host range specifity study showed that of the 3 rhizobial biovars Vicia faba rhizobia were the most host discriminative rhizobia that formed less number of nodules on other host plants. Thus, Lens culinaris and Pisum sativum rhizobia showed almost similar host discriminative capacity. Isolates differentiated by morphological, acidlalkali production capacity and growth characteristics into 4, 2 and 4 categories, respectively. Approximately 40 % of the total isolates similarly exhibited a colony category of mucoid moisture, with circular shape, white opaque color, and raised structure. However, Lens culinaris rhizobia were distinguished apparently by two morphological characteristics. In general, 92% of the indigenous rhizobia isolates examined in this study were fast to very fast growing types acid producing types with overall MGT of 5.88 to 5.9 h- Eighty-three representative indigenous isolates and 4 reference strains were examined for their physiological characteristics such as Am, STL, IAA and C SUP and isolates showed variable response. Few rhizobial isolates were able to grow on acid media of pH 4.75 - 6.00. Two Vicia faba and one Pisum sativum rhizobia were the most acid tolerant isolates that grew at pH 4.75. A total of four Vicia faba and two Pisum sativum rhizobia were identified to be acid tolerant isolates. In contrary, some isolates of central and northwest highland origins were very sensitive to slightly low pH media of 6. TALI 399 grew apparently on pH 5.5 the reset ph>5.5. Some isolates of the same agro-ecology found to have uniform Am. The response of representative isolates to growth-inhibiting salt (NaC1) concentrations showed relatively law variations among isolates. Most (92%) isolates were able to grow well at salt concentration of 0.1 % and less. The rest 54 % isolates remained unchanged. Almost 78% isolates were tolerated to NaCl upto 0.2%. However, apparently, 3 isolates survived at the highest NaCl concentration of 0.3%. Isolates were homologues with the increased similarity level (>0.60) and 17 isolates had shown identical response with that of reference strains. The IAA concentration for the investigated isolates showed that indigenous isolates varied greatly in their IAA production capacity and formed 17 clusters. The IAA concentration reached up to 25.92 mg L-' with a mean of 9.9 mg L-'. In general, IAA producing capacity of isolates was remained the best indicator to distinguish and group rhizobial isolates. Isolates cluttered into 5 clusters at increased similarity level of >0.60. IAA was the best indicator among the tested physiological parameters for the divergence of isolates among each other. With respect to C SUP, most isolates preferred polyols, monosaccharide, and disaccharides as their first, second, and third choice carbon sources, respectively. Lentil rhizobia were indifferent for about 6 of the 8 C sources. Also, results from the current study showed great diversity among isolates with respect to their JAR capacity, making this test useful for distinguishing among isolates. Thirty-three isolates have shown multi-resistant characteristics and formed 18 identical antibiotic resistance profiles. However, number of similar clusters varied with an increase in similarity level of 0.60. Thirteen isolates were found significantly divergent from the bulk of isolates examined. Faba bean and field pea rhizobia had shown more or less uniform IAR capacity, whilst lentil rhizobia showed different IAR capacity for the examined antibiotics. DNA fragment analysis carried out for 95 representative isolates have shown a total of 83, 79, and 75 fragment patterns for RAPD-PCR, HaeIII and MspI RE-RFLPs, respectively. These two enzymes per se showed highly polymorphic and distinct DNA profiles indicating the divergence of Rhizobium isolates. RE digestion of Lens culinaris rhizobia with both enzymes yielded single PCR products with approximately 750 base pairs while the single band for Vicia faba and Pisum sativum yielded larger fragment of up to 1800 base pairs. Majority (76.17 %) showed significant genetic similarity, while the rest (23.83 %) isolates were divergent among each other. The RAPD-PCR and RE digestions methods formed 18, 13 and 20 clusters respectively. Hence, the DNA profile analysis showed that isolates were distinctly divergent among each other at higher similarity level of >O.60. Field inoculation experiment on lentil showed that elite inoculant strain EAUOO and imported commercial strain TALI402 in both single as well as mixed inoculant form(s) showed significant (P<0.05) increase in seed yield, yield components, nodulation and symbiotic growth of lentil. The study demonstrated that inoculant type of rhizobial strain sounds better than apparent use of different form(s) (single or mixed inoculants) of inoculants under lentil. Moreover, divergent of rhizobia within Rhizobium leguminosarum bv. viciae nodulating CSFLs, the field performance of the 2 strains (EAUOO and TAL1402) and the presence indigenous rhizobia that have similar characteristics with strain EAUOO and TALI402 indicates the future potential for identification of new competitive and efficient Rhizobium leguminosarum strains for the country.